Molecular mechanisms of drug resistance in M. tuberculosis - Cirillo, Daniela (Henry Stewart Talks, 2013)
Drug resistant tuberculosis epidemic, Mechanisms of drug resistance in M.tuberculosis, Mechanisms of drug resistance to first and second line antitubercular drugs, Considerations on currently available molecular tests for the diagnosis of drug resistant tuberculosis